Discrete Heat Equation model of Rod by Partial Fibonacci Difference Operator with shift values - Pinelas, Sandra; Britto Antony Xavier, G.; John Borg, S.; Jaraldpushparaj, S. (International Journal of Engineering and Technology, 2018)
Partial Fibonacci difference equation is introduced and subjected to investigation in discrete heat equation by having recourse to Fibonacci difference operator with shift values in this paper. By having Fourier law of cooling as its basis, the heat transfer in the long rod is investigated and the solutions obtained are validated by MATLAB.Â Â